A survey of energy-aware real time scheduling tools - Ahmad, Idawaty (Society of Digital Information and Wireless Communications (SDIWC), 2015)
This paper gives a brief survey on the existing simulation tools that are available to further investigate the performances of energy-aware real time scheduling algorithms. The previous work from Y. Chandarli et.al, suggested four properties for a real time scheduling tools to become a reference tool by the real time scheduling community. This paper compares the properties of the most recent real time scheduling tools considering to the above mentioned properties from simulation software perspective. Programming language is one of the important properties that influence the popularity of these tools. This criteria is compared between these tools. Java language is observed to dominate the development of these simulation tools.